The experience of occupational engagement of chronically homeless persons in a mid-sized urban context. Issue 2 (3rd April 2017) - Marshall, Carrie Anne; Lysaght, Rosemary; Krupa, Terry
ABSTRACT: Background: Chronic homelessness is a growing problem in many Western nations. Few studies have explored the occupations of chronically homeless persons, and most of this research has sampled from large metropolitan areas. Purpose: This research sought to explicate the meaning and experience of occupational engagement for homeless persons in a mid-sized urban context. Method: Interpretive phenomenology informed qualitative interviews with 12 chronically homeless participants. Analysis used a modified version of Colaizzi's (1978 ) methodology. Findings: Themes highlight the experience and meaning of the unique occupations of chronically homeless persons. Altruistic and productivity occupations held particular meaning. Occupational alienation, and the boredom that resulted, severely influenced the psychological well-being of participants. The need to engage in meaningful occupations is powerful, to the extent that it can supersede the perceived importance of housing. Implications: An occupational perspective is a valuable contribution to a broader dialogue on homelessness, and may contribute to a more comprehensive strategy for addressing this problem. Future research should explore boredom and its association with substance use, and ways of enhancing opportunities to include chronically homeless persons in employment and other meaningful occupations.